Alkaloids and cyclopeptides from the marine-derived fungus Aspergillus sp. M512 - Quynh, Do Thi; Tuan, Cao Duc; Chuc, Dang Van; Lien, Hoang Thi Hong; Huyen, Le Khanh; Minh, Le Thi Hong; Cuong, Pham Van; Hung, Nguyen Van; Kim, Young Ho; Huong, Doan Thi Mai (Vietnam Journal of Science and Technology, 2020)
In the course of our screening program, the EtOAc extract of an Aspergillus sp. (strain M512) exhibited antimicrobial activities against three Gram Positive bacteria, and one yeast strain. This paper reported the isolation and structural elucidation of seven secondary metabolites including two alkaloids (1-2) and five cyclodipeptides (3-7) from culture broth of Aspergillus sp. M517. All isolated compounds were evaluated for their antimicrobial activity against a panel of clinically significant microorganisms. Except compound 1 and 2, with MIC values ranged from 32 to 128 μg/mL, five other compounds do not show inhibition activities against tested microorganisms.